Case report: A mesocolic lymphangioma in a 14-year-old child resected by laparoscopic surgery - Feng, Xuping; Chen, Xinyang; Feng, Qingbo; Liu, Xiaoyin; Li, Hancong; Chen, Hao; Cai, Zhaolun; Li, Jiaxin (Frontiers in Oncology, 2022)
Introduction: Cystic lymphangioma is a benign malformation tumor of the lymphatic system. Its location is variable, and mesocolonic localization remains extremely rare. Case Presentation: We report a case of right mesocolon giant cystic lymphangioma in a previously healthy 14-year-old boy who was successfully managed through a minimally invasive laparoscopic excision. The patient presented with 8 months of dull abdominal pain, sporadic, located on the peri-umbilicus, exacerbated for a month. An abdominal computed tomography (CT) revealed a large, multiseptated cystic mass on the right mesocolon. Right mesocolic excision using a laparoscope was performed on this patient. He was discharged on the fifth day without complications. Recurrence was not detected in three months of follow-up. Conclusion: Cystic lymphangiomas in the mesocolon are rare benign neoplasms that pose diagnostic challenges. Complete resection is the optimal option for diagnostic confirmation and recurrence prevention. Laparoscopic surgery is feasible for children with mesocolonic lymphangioma